26 Poetas argentinos 1810-1920 - GHIANO, Juan Carlos (EUDEBA, 1960)
CONTENIDO :LOPEZ Y PLANES, Vicente; LUCA, E.DE; HIDALGO, B.; VARELA, JUAN C.; ECHEVERRIA, E.; GUTIERREZ, Juan M.; MARMOL, J.; ASCASUBI, H.; DEL CAMPO, E.; HERNANDEZ, J.; GUIDO Y SPANO, C.; GUTIERREZ, R.; ANDRADE, O.; OBLIGADO, R.; PALACIOS, P.B.; ALMAFUERTE; DIAZ, L.; LUGONES, L.; CARRIEGO, E.; BANCHS, E.; ROJAS, R.; ARNIETA, Rafael; CAPDEVILLA, A.; MARASSO, A.; FERNANDEZ MORENO, B.; STORNI, Alfonsina; GUIRALDES, Ricardo